Ett gammalt kulturlandskap i Vindelfjällen - Jansson, Ulrika (2005)
Humans have inhabited mountainous areas in northern Sweden since the end of the last glacial period, ca 8000 B.P., and their presence has marked the landscape in various ways. Older traces include the remains of hearths and dwelling sites, but there are also remains, such as culturally modified trees (CMT's), resulting from more recent activities in forested areas. This study aimed to document how people, both indigenous Sami's and Swedish settlers, have used an area northwest of Ammarnäs in Västerbotten, during the last 300 years, and what traces their activities have left in the area. I used historical records as well as an inventory of CMT's in the area to address this aim. Historical records of Sami activity are meagre, but it is clear that the people of the Ran and Gran Sami villages utilized the area long before 1500 A.D. Sami people peeled pine trees to use the inner bark as food and for storage of reindeer sinews, and the resultant Smi bark peelings can still be found in the forest. The first Swedish settlers in Ammarnäs arrived at the beginning of the 19th century, according to historical records. This is also indicated by trail markings and other CMT's and by evidence of haymaking. Both Sami and settlers utilized birch-bark as roof cover, as evidenced by birch-bark peelings in the area. There is also a trail though the area, which was make when the settlers were trading with Norway. During an inventory of the area, I discovered 220 CMT's of which 131 were birch-bark peelings and 29 were Sami bark peeling. However, during logging, which occurred around the 2nd World War, many old pines were removed, potentially removing and destroying a large proportion of the original Sami bark peelings. Of the CMT's documented during this study, the birch-bark peelings are the ones most likely to remain as a phenomenin, since they are still created by people using the birch-bark in handicraft. Our nature reserves have, as shown in this and in other studies, not only natural, but also cultural values. The mountain areas have a history many people have little knowledge about. The traces of old land use still left in these areas can give us further knowledge about the history of these areas, and we are obliged to save this cultural heritage for generations to come.